The wedding shop [large type] - Hauck, Rachel, 1960- (Thorndike Press, 2016)
Cora Scott runs the popular Wedding Shop in 1930s Heart's Bend, Tenn., attracting brides-to-be from all over the South. She waits anxiously for her lover, riverboat captain Rufus St. Claire, to return and fulfill his promise to marry her, but as the months slip away with no sign of him, a local farmer patiently proves his dedication and worth. In the present day, former Air Force Capitan Haley Morgan returns home to Heart's Bend from her California base, after a childhood friend's sudden death from brain cancer sends her reeling. When they were young, the two made a pact to one day reopen the abandoned wedding shop that they would sneak into and imagine what it would be like to be married. To overcome her grief and move forward with her career, Haley decides she will fulfill the pact and reopen Cora's charming store. Hauck (The Wedding Dress) seamlessly switches back and forth in this redeeming tale of a shop with healing powers for the soul. As Cora and Haley search for solace and love, they find peace in the community of the charming shop. Hauck succeeds at blending similar themes across the time periods, grounding the plot twists in the main characters' search for redemption and a reinvigoration of their wavering faith. In the third of her winsome wedding-themed standalone novels, Hauck focuses on the power of community to heal a broken heart.